2008
DOI: 10.1111/j.1469-8137.2008.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physiology of adventitious root formation in Petunia hybrida cuttings: involvement of wound response and primary metabolism

Abstract: Summary• Adventitious root formation (ARF) in the model plant Petunia hybrida cv. Mitchell has been analysed in terms of anatomy, gene expression, enzymatic activities and levels of metabolites. This study focuses on the involvement of wound response and primary metabolism.• Microscopic techniques were complemented with targeted transcript, enzyme and metabolite profiling using real time polymerase chain reaction (PCR), Northern blot, enzymatic assays, chromatography and mass spectrometry.• Three days after se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
186
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(218 citation statements)
references
References 65 publications
22
186
1
1
Order By: Relevance
“…The protein product of the gene GH3.11, which is also called JASMONIC ACID RESISTANT1 (JAR1), conjugates JA to Ile, producing jasmonoyl-L-isoleucine (JA-Ile), the active signaling molecule recognized by the F-box receptor CORONATINE INSENSITIVE1 (COI1) (Fonseca et al, 2009). In addition, methyl jasmonate was shown to inhibit root growth in Arabidopsis (Staswick et al, 1992), and JA transiently accumulated at the base of Petunia hybrida stem cuttings after mechanical wounding but very rapidly returned to its basal level before adventitious root formation took place (Ahkami et al, 2009). Fattorini et al (2009) showed that submicromolar amounts of methyl jasmonate promoted adventitious root development from thin cell layers of tobacco (Nicotiana tabacum).…”
Section: Online)mentioning
confidence: 99%
“…The protein product of the gene GH3.11, which is also called JASMONIC ACID RESISTANT1 (JAR1), conjugates JA to Ile, producing jasmonoyl-L-isoleucine (JA-Ile), the active signaling molecule recognized by the F-box receptor CORONATINE INSENSITIVE1 (COI1) (Fonseca et al, 2009). In addition, methyl jasmonate was shown to inhibit root growth in Arabidopsis (Staswick et al, 1992), and JA transiently accumulated at the base of Petunia hybrida stem cuttings after mechanical wounding but very rapidly returned to its basal level before adventitious root formation took place (Ahkami et al, 2009). Fattorini et al (2009) showed that submicromolar amounts of methyl jasmonate promoted adventitious root development from thin cell layers of tobacco (Nicotiana tabacum).…”
Section: Online)mentioning
confidence: 99%
“…Ultrastructural analysis of the origin of adventitious roots in cuttings of the distant relative petunia (Petunia hybrida) show their origin from cell divisions within the cambium layer itself (Ahkami et al, 2009) in a manner distinct from the dedifferentiation of cortical parenchyma in dodder. At no point in the dodder life cycle does the plant possess a normal root.…”
Section: Origin Of Haustoriamentioning
confidence: 99%
“…In Arabidopsis tissue culture where explants incubated on auxin-rich callus-inducing medium (CIM) were subsequently transferred on to cytokinin-rich shoot-inducing medium (SIM) (Valvekens et al, 1988), intact, uncut plants hardly regenerated shoots at all (Iwase et al, 2015), thus demonstrating a requirement for wound stimuli in initiating regeneration. Wounding induces numerous cellular responses, including the production of plant hormones (Ahkami et al, 2009), loss of cell-to-cell communication and disruption of long-distance signaling .…”
Section: Wound Stress As a Trigger For Regenerationmentioning
confidence: 99%